Ageism and Depression: Perceptions of Older People as a Burden in China. (March 2016) - Bai, Xue; Lai, Daniel W.L.; Guo, Aimei
Abstract : Traditional values and beliefs about aging and older adults appear to be changing in China, as a result of transformations in family structure and social system in the context of rapid modernization and economic growth. This study examined the effects of burden views toward Chinese older adults on their depressive symptoms based on a secondary analysis of data collected from a sample of 954 Chinese adults aged 60 and over in Jiangsu Province. After controlling for sociodemographic, health, and family relationship variables, results of hierarchical multiple regression analysis revealed that participants with stronger views of older people as a burden to family and society were at higher risk of depressive symptoms. Findings of this study can inform the development of policies and programs to address mental health challenges facing older adults in China, focusing on helping them get rid of the burden views about older people, improving family relationship quality, and fostering a positive attitude toward aging in the wider society.